2016
DOI: 10.1002/oby.21441
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat diet feeding alters olfactory‐, social‐, and reward‐related behaviors of mice independent of obesity

Abstract: Objective: High-fat diet (HFD) consumption causes obesity, which is associated with well-known increased health risks. Moreover, obesity has been associated with altered sensorimotor and emotional behaviors of humans and mice. This study attempted to dissociate the influence of HFD-induced obesity on behaviors from the influence of HFD consumption itself. Methods: C57BL male mice were randomly allocated to a low-fat diet (LFD) group, an HFD-induced obesity (DIO) group, or a pair-fed HFD-feeding nonobese (HFD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
62
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 39 publications
11
62
2
5
Order By: Relevance
“…Despite the animals in groups P and especially those in group G showing less weight gain after 72 or 182 days treatment, the behavior in EPM was similar to animals in groups C, GL and L. These data match those in the literature when animals were treated with a diet rich in sucrose [5,6], rich in protein [20] and rich in lipids [7,9,10,16] and also showed no change when tested in the EPM. However, the diet rich in lipids had an anxiolytic [13] and anxiogenic effect [11,12,14,15,17].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite the animals in groups P and especially those in group G showing less weight gain after 72 or 182 days treatment, the behavior in EPM was similar to animals in groups C, GL and L. These data match those in the literature when animals were treated with a diet rich in sucrose [5,6], rich in protein [20] and rich in lipids [7,9,10,16] and also showed no change when tested in the EPM. However, the diet rich in lipids had an anxiolytic [13] and anxiogenic effect [11,12,14,15,17].…”
Section: Discussionsupporting
confidence: 87%
“…The assessment of anxiety in animals treated with obesogenic diets (rich in carbohydrates [5,6], lipids [7][8][9][10][11][12][13][14][15][16][17] and carbohydrates and lipids [18,19]) is controversial. For some authors, the diet did not change the behavior in the EPM [5][6][7]9,10,16,20], for others it increased [8,11,12,14,15,[17][18][19] or reduced anxiety [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some observed high alcohol intake in fat-preferring rats, following high-fat diet exposure or injection of dietary lipids (Barson et al, 2009; Carrillo et al, 2004; Krahn and Gosnell, 1991), while others reported no correlation (Prasad et al, 1993) or blunted alcohol intake (Takase et al, 2016). However, to our knowledge, this is the first examination of alcohol intake following prolonged episodes of binge-like feeding of a nutritionally complete high-fat diet.…”
Section: 0 Discussionmentioning
confidence: 99%
“…High-fat diet (HFD) consumption is associated with cognitive impairment, increased aggression and altered social- and reward-related behaviors in mice (Hilakivi-Clarke et al, 1996; Pistell et al, 2010; Takase et al, 2016). A mouse model of n-3 polyunsaturated fatty acids (PUFAs) deficiency resulted in defective spatial learning and memory tasks, with increased depressive-like behavior (Larrieu et al, 2012; Moranis et al, 2012).…”
Section: Microglial Perturbations During Brain Developmentmentioning
confidence: 99%